An experimental case study on designing adaptive apparel based on the special clothing needs and preferences of selected adult male and female hemiplegic patients living in Metro Manila - Ignacio, Corinne Carreon; Escano, Maria Monica R. (2001.)
The study answers the need for designing special clothing which requires the use of one hand with minimal or no assistance in putting on clothes. It aims to come up with designs and have them constructed into garments of hemiplegics to consequently enable them to be independent in donning and doffing their clothes. The study is partly experimental and partly descriptive in nature. It made use of the flexible characteristics of an experiment and a case study. An experimental study, Venancio B. Ardales (1992) explained, allows the manipulation of variables. On the other hand, a case study, as expounded by Robert K. Yin (1994), may use multiple sources of evidence. Such examples of which are documents, interviews and direct observation. Using this combination, manipulation of variables, the use of varied sources of evidence and the integration of a pretest-posttest was made possible. The prospective respondents are patients from the Occupational Therapy Section (OTS) under the Rehabilitation Therapy Department of the Veterans Memorial Medical Center in North Avenue, Quezon City. They were primarily briefed on what study was about, what were asked of them and what they can expect from it. They signed a letter of consent as a written approval and proof of their participation. During the pretest the patients answered a set of questionnaires to assess the garments they usually wear and to indicate their clothing needs and preferences. The garment designs and materials specifications were discussed in detail prior to taking the body measurements. Fabric samples were presented to the respondents before purchasing the materials. after construction, the patients were taught on how to don and doff the garments before taking them home for one-week "test wear" period. After which, the custom-made garments were evaluated for their function, fit and ease of wear. To understand a typical hemiplegic patient, documents on hemiplegia, occupational therapy treatment, rehabilitation and other related topics were reviewed and taken into careful consideration. Occupational Therapy practitioners teach hemiplegics a method of donning and doffing clothes aptly coined "one-handed dressing technique." Variations of this method were developed to help patients be independent and utilize their unaffected side in dressing. Nellie Thornton (1990) and Lorraine Williams Pedretti (1996) gave some guidelines in construction of special garments for hemiplegics. Conceptualizing garments for hemiplegics was a great challenge for it entails various considerations like price, climate, color and style preferences, lifestyle, and independence. Influences of factors such as demographic, economic and climactic conditions reflect on the selection and description of the subjects' preferred items of clothing. It was observed that patients show varying degrees of independence in going about some of their ADL (Activities of Daily Living). This is one factor why no two garments are exactly alike in design and manner of dressing, besides considering the individual needs and tastes in clothing. Garment details that have been added enable the respondents easily don and doff their clothes. However, the garments still require some minor alterations to improve their functionality and fit. With the construction of custom-made apparel for hemiplegics, there is an improvement on their independence while donning and doffing. Despite having an existing method for dressing, it was realized that by altering the garment designs, other techniques are introduced and that the patients were able to dress easier and faster with little or no assistance at all.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Hemiplegics -- Clothing -- Design